Diplomatic Strategies of Rising Nations in the Global South
XIX, 478 p. 1 illus.
Keywords: “While much has been written about rising powers in world order, the ‘Rise of the Rest’ is a broader and more complex notion – with a wider cast of nations and greater range of foreign policy approaches - that few studies have systematically analyzed. This volume admirably fills this gap with carefully selected cases from around the world.” Amitav Acharya, Distinguished Professor, American University, Washington DC “This volume offers a wealth of insight on rising countries in the global south. Collectively, the chapters demonstrate why these countries deserve more scholarly attention – not only in their own regions but globally. This volume is a must-read for anyone who wishes to achieve a more comprehensive – and global – understanding of the drivers of states’ external involvement.” Marijke Breuning, Regents Professor, University of North Texas, USA “At a time when the International Relations field still suffers from a Western-centered focus, this volume provides the needed and overdue balance to grasp global order and its contemporary challenges. Thought-provoking and highly needed.” Bahgat Korany, Professor of Political Science, American University in Cairo "This volume makes invaluable contributions to our understanding of the foreign policies of states beyond the traditional great powers, and of the fundamental—and growing—roles that the Global South plays in international relations." -Tom Long, Reader in International Relations, University of Warwick At a time of change in the international system, this book examines how and why nations from the global south have begun to rise in influence, and the probable impact on global governance. The rise of China, India, and other leading states offers a glimpse at a future in which a diverse multipolarity can become the norm. The contributors to this book discuss the prospects for, and the sustainability of, the rise in influence of global south states across Asia, Africa, and Latin America, through the lens of foreign policy analysis and diplomacy. Jacqueline Braveboy-Wagner is Professor Emeritus of Political Science in the Graduate School of the City University of New York. She is the author of twelve books, past president of the Caribbean Studies Association, and founder of the Global South Caucus of the International Studies Association.